Unveiling the Final Report Writing Journey: A Phenomenological Study of Final-Year Vocational EFL Students - Beni Wijaya; Zakaria; Munaja Rahma; Darmaliana; Sri Endah Kusmartini; Eli Yeny (International Journal of English and Applied Linguistics (IJEAL), 2026)
For final-year English as a Foreign Language (EFL) students, producing final reports is an important academic milestone. However, little research has been done on how students feel about this process in vocational higher education settings. The purpose of this study was to look into the actual experiences of final-year Diploma III EFL students when preparing their final reports. Twelve final-year students from Politeknik Negeri Sriwijaya's English Study Program participated in semi-structured interviews to gather data using a qualitative phenomenological approach. Thematic analysis was then used for analysis. Academic and research-related difficulties, emotional experiences, sources of support, coping mechanisms, and academic and personal development were the five main themes that emerged from the findings. Finding pertinent references, writing literature reviews, analyzing data, structuring ideas, and using academic writing conventions in English were all challenges faced by the participants. Stress, perplexity, frustration, exhaustion, anxiety, and self-doubt frequently accompanied these difficulties. However, students were able to handle them and maintain their motivation with the help of peers, family, supervisors, and online resources. Goal-setting, time management, asking for help, sticking to regular work schedules, and self-motivation were among the coping mechanisms used by them. The final report writing process was seen as a life-changing event that improved research competency, academic writing skills, critical thinking, independence, resilience, confidence, and problem-solving abilities despite the obstacles. The study comes to the conclusion that writing final reports is a significant learning experience that advances students' academic, personal, and professional development in addition to being a graduation requirement.